Successful Management of Dental Crowding with Removable Orthodontic Appliances: A Case Series - Adrianti Primata Ayu; Agnes Maureen Senjaya; Muhammad Rifai Hasbi; Labiyan Asri Laili; Dwita Pratiwi; Muhammad Sulaiman Kusuma Adiwirya; Sigit Handoko Utomo (Journal of Indonesian Dental Association, 2026)
Introduction: This case series evaluated the efficacy of removable orthodontic appliances in managing mild to moderate anterior dental crowding. Objective: To determine the association between payment scheme, insurance participation, and economic status with orthodontic appliance preference among undergraduate students in West Jakarta. Case Report: Case I: A 21-year-old female with a Class I skeletal pattern. Clinical examination revealed a moderate crowding in the maxillary arch and a mild crowding in the mandibular arch with overjet  and overbite, except teeth 12 and 32. The patient was treated with a removable orthodontic appliance featuring an expansion screw and active components. Post-treatment demonstrated a reduction of the overjet, an increase in the overbite, and significant correction of anterior crowding in both arches. Case II: A 22-year-old patient with a chief complaint of misaligned lower front teeth three months after completing fixed orthodontic treatment. The patient Class II canine relationships, 3.5 mm overjet and mild crowding in both arches. The patient was treated with a removable orthodontic appliance, and successfully corrected the lower arch anterior crowding and reduced the overjet. Disscussion: The two cases demonstrated the effective use of a removable appliance in addressing different orthodontic problems. Combined with techniques such as interproximal reduction and regular follow-up, successfully improved dental alignment, overjet, overbite, and smile appearance. Conclusion: Removable orthodontic appliances offer a viable treatment modality for mild to moderate cases of dental crowding. This cases presented provide evidence supporting their effectiveness in improving dental alignment, thereby contributing to enhanced esthetics and patient confidence.